Evaluation of diverse germplasm lines/cultivars for yield and yield components in blackgram (Phaseolus mungo) - SHARMA, B L; SINGH, D P; SINGH, K H (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted during 1993-95 on the extent of variability in 87 and 30 lines/cultivars in the blackgram (Phaseolus mungo L.). Based on the performance in 1993,5 surperior lines for each character as well as for yield /plant were selected for the evaluation in 1995. Large extent of variability was observed for all the characters in both the years except for days to maturity. Some of the lines/cultivars were superior to the check (s) for different character (s). Whereas ’HPU 4’ was better than the best check,ie ’Pant U 19’ in the replicated yield trial. Thirty lines/cultivars were represented by 4 distinct morphological groups.